An enhanced mobile internet protocol version 6 (IPv6) with multicast function and hierarchical design. - Khatun, Sabira (2006)

(untitled)
The present invention relates to Internet Protocol version six (IPv6) as a wireless network infrastructure. More particularly provides a method to improve the handover delay in Mobile IPv6 so as to offer uninterrupted on-line experience in network applications such as in entertainment, games, video conferencing or video streaming while on the move. Mobile IPv6 mechanism requires some handover algorithm when it changes its point of attachment in the Internet.An enhanced micro mobility handover algorithm is developed on top of mobile IPv6. This invention solves the problem of long delay and packet loss incurred during handover through enhancement of handover management in Mobile IPv6. It integrates hierarchical concept and multicast function. Hierarchical design is used to shield the micro mobility from macro mobility in order to reduce location update signal and signalling traffic within micro level network while multicasting is used to send packets to Mobile Node (MN) through base stations that are near to MN. This reduces handover delay that causes packet lost when MN is roaming. A representative system (real-time test-bed) comprises of both software and a hardware element has been developed.